[Rezension von Birte Bös and Lucia Kornexl (eds.). Changing genre conventions in historical English news discourse] - Landert, Daniela (de Gruyter, 2017)
Birte Bös and Lucia Kornexl (eds.). Changing genre conventions in historical English news discourse. Advances in historical sociolinguistics 5. Amsterdam/Philadelphia, PA: Benjamins, 2015, xv + 254 pp., € 99.00/$ 149.00